BIOM-41. LIVE-CELL IMAGING SHOWS UNEVEN SEGREGATION OF EXTRACHROMOSOMAL DNA ELEMENTS AND TRANSCRIPTIONALLY ACTIVE EXTRACHROMOSOMAL DNA CLUSTERS IN CANCER. (12th November 2021) - Yi, Eunhee; Gujar, Amit; Guthrie, Molly; Kim, Hoon; Zhao, Dacheng; Johnson, Kevin; Amin, Samirkumar; Das, Sunit; Jillette, Nathaniel; Clow, patricia; Cheng, Albert; Verhaak, Roel
Abstract: Oncogenic extrachromosomal DNA elements (ecDNAs) promote intratumoral heterogeneity, creating a barrier for successful cancer treatments. The underlying mechanisms are poorly understood and studies are hampered in part by a lack of adequate tools enabling studies of ecDNA behavior. Here, we show that single-cell ecDNA copy numbers greatly vary between tumor cells, both in vitro and in patient glioblastoma specimens, suggesting uneven ecDNA segregation during mitosis. We established a CRISPR-based approach which leverages unique ecDNA breakpoint sequences to tag ecDNA with fluorescent markers in living cells. Applying this method during mitosis revealed disjointed ecDNA inheritance patterns, providing an explanation for rapid ecDNA accumulation in cancer. Post-mitosis, ecDNAs tended to cluster and clustered ecDNAs colocalized with RNA polymerase II, promoting transcription of cargo oncogenes. Our observations provide direct evidence for uneven segregation of ecDNA and sheds new light on mechanisms through which ecDNAs contribute to oncogenesis.